Alice of Antioch and the rebellion against Fulk of Anjou - Adriana Almeida (Medievalista)
This article focuses on the political turmoil in the Latin East in the first half of the 12th century. It means to illustrate how the description William of Tyre left us of Alice, second daughter of king Baldwin II of Jerusalem, as a woman who betrayed her family, her place and her sex, can also be read to its contrary, and even help to identify this woman as a fundamental key in the opposition of some of the established nobility to the politics of the new king, Fulk of Anjou.